EFEKTIVITAS INDONESIA DALAM PENENTUAN HARGA CPO (CRUDE PALM OIL) DI PASAR KOMODITAS INTERNASIONAL TAHUN 2007-2011 - Lestari, Danty Ayu; Fachri, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes how the effectiveness of the Indonesia government adoopted a policy that Indonesia can be a determinant of the price of CPO in the international commodity market. Indonesia is the world's largest palm oil producer since 2007, but global CPO market still refers to the physical market and the futures market Rotterdam / derivatives Malaysian Derivative Exchange (MDEX) in Kuala Lumpur as the CPO's market price. Indonesia also determines the price and has a strong position in the international palm oil trade but not effective yet, the trade liberalization needs to be done to reduce export duties, strengthen coordination between government, employers and local communities, in addition to the need for support from the government to build infrastructure and strengthen negotiations at international level.Keywords: Commodity, CPO, Price Reference, Rotterdam